2016
DOI: 10.1097/bpo.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Botulinum Toxin A in Children Undergoing Lower Limb Lengthening and Deformity Correction

Abstract: Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…. and m = mean value; bars = SD; BtX-A = botulinum toxin type A was 3.6 IU/kg (range, 2.9-5.0 IU/kg) which is a smaller dose than those used in previous studies [9][10][11]. Therefore, a different dose, dilution, or schedule, or the use of repeated injections, may provide improvement.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…. and m = mean value; bars = SD; BtX-A = botulinum toxin type A was 3.6 IU/kg (range, 2.9-5.0 IU/kg) which is a smaller dose than those used in previous studies [9][10][11]. Therefore, a different dose, dilution, or schedule, or the use of repeated injections, may provide improvement.…”
Section: Discussionmentioning
confidence: 92%
“…More specifically, extension of the hip and flexion of the knee decrease because of tightness in the quadriceps [1,3,25]. To prevent this complication, BtX-A injections seem to be an appealing option; however, prior studies have disagreed regarding whether BtX-A is effective [9,10,17]. Previously, Lee et al [17] reported that BtX-A injection in the calf muscle during tibial lengthening was not effective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations